2018
DOI: 10.7759/cureus.2268
|View full text |Cite
|
Sign up to set email alerts
|

Parent Knowledge and Perceptions of Concussion Related to Youth Football

Abstract: IntroductionThere is increased concern about concussion in youth athletes, yet there is little research on parent knowledge of concussion.Purpose The purpose of the current study was to investigate attitudes to and knowledge of concussion among parents of youth football players.MethodsWe surveyed 180 parents/guardians of youth football players, ages 5-12, regarding their knowledge and beliefs concerning concussion.ResultsWe found that the vast majority of respondents (86%) had confidence in their ability to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
4
9
0
1
Order By: Relevance
“…However, results from questions surrounding danger sign recognition and concussion recovery tactics were poor in both groups. This is similar to assessments performed by Rieger et al, [9] who showed great variability in parental input concerning aspects of recovery. These may be important areas on which to focus educational efforts, as they may affect management initiation, as well as return to play.…”
Section: Discussionsupporting
confidence: 89%
“…However, results from questions surrounding danger sign recognition and concussion recovery tactics were poor in both groups. This is similar to assessments performed by Rieger et al, [9] who showed great variability in parental input concerning aspects of recovery. These may be important areas on which to focus educational efforts, as they may affect management initiation, as well as return to play.…”
Section: Discussionsupporting
confidence: 89%
“…A greater urgency for an initial visit may also be due to mandated medical clearance in concussion legislation and increased education for parents about concussion and its consequences. [37,38] A shorter time to rst visit following concussion is associated with faster recovery times in previous studies, so future studies should investigate how insurance type affects differences in care received until symptom resolution. [14,39] Another possible explanation for the observed decrease in average time to initial concussion visit is an increase in availability of concussion care at NCH, although this study did not collect data on that aspect.…”
Section: Discussionmentioning
confidence: 89%
“…Although concussions among younger athletes is an important public health issue, much remains unknown on the long-term impact of sports-related concussion in children and how parents and health care providers can appropriately manage them [8, 9]. A recent study aiming to explore parents’ knowledge of concussion among young football players aged 5–12 years old found that misconceptions about concussion commonly existed among parents [10].…”
Section: Introductionmentioning
confidence: 99%